Cyril and Theodoret on the Temptation of Christ: An Imaginary Dialogue Between Alexandrian and Antiochene Christological Positions - Kupán, István Pásztori (Perichoresis, 2022)
In this paper some parallelisms and differences are presented between two ancient theological traditions concerning their model of Christ by comparing two representative figures of both schools, namely Theodoret of Cyrus and Cyril of Alexandria. Since the Christology of the two authors could not be compared in detail within such a paper, the investigation resumes itself to the mode how they interpret the Lord’s Temptation by the devil in the wilderness. The works involved in the analysis include Theodoret’s treatise On the incarnation written in 431 before the Council of Ephesus, the fragments of Cyril’s Commentary on Matthew as well as his Commentary on Luke. The doctrinal conclusion of this comparison is that the two traditions represented by these illustrious theologians—despite their conspicuous and undeniable differences— signify rather complementary than flatly opposing views and that the two ancient traditions have found their revival even in the sixteenth century, and continue to influence the theologians of our time. This is why the author considers Chalcedon as being a corridor (in which both traditions can walk side by side whilst respecting the limits set by ‘the columns’, i.e. the four famous expressions) rather than a narrow path or a tightrope-walking, where only one is able to go through.